A novel automatic regulatory device for continuous bladder irrigation based on wireless sensor in patients after transurethral resection of the prostate: A prospective investigation. Issue 52 (December 2016) - Ding, Aimin; Cao, Huling; Wang, Lihua; Chen, Jiangang; Wang, Jian; He, Bosheng
Abstract: Background: Benign prostatic hyperplasia is a common progressive disease in aging men, which leads to a significant impact on daily lives of patients. Continuous bladder irrigation (CBI) is a supplementary option for preventing the adverse events following transurethral resection of the prostate (TURP). Regulation of the flow rate based on the color of drainage bag is significant to prevent the clot formation and retention, which is controlled manually at present. To achieve a better control of flow rate and reduce inappropriate flow rate–related adverse effects, we designed an automatic flow rate controller for CBI applied with wireless sensor and evaluated its clinical efficacy. Methods: The therapeutic efficacy was evaluated in patients receiving the novel automatic bladder irrigation post-TURP in the experimental group compared with controls receiving traditional bladder irrigation in the control group. Results: A total of 146 patients were randomly divided into 2 groups—the experimental group (n = 76) and the control group (n = 70). The mean irrigation volume of the experimental group (24.2 ± 3.8 L) was significantly lower than that of the controls (54.6 ± 5.4 L) ( P < 0.05). Patients treated with automatic irrigation device had significantly decreased incidence of clot retention (8/76) and cystospasm (12/76) compared to controls (21/70; 39/70, P < 0.05). There was no significant difference between the 2 groups with regard to irrigation time (28.6 ± 2.7 vs 29.5 ± 3.4 hours, P = 0.077). Conclusion: The study suggests that the automatic regulating device applied with wireless sensor for CBI is safe and effective for patients after TURP. However, studies with a large population of patients and a long-term follow-up should be conducted to validate our findings.